# (x^2+3)(x^3+2x^2+3x+6)+(2x^3+3)=

## Simple and best practice solution for (x^2+3)(x^3+2x^2+3x+6)+(2x^3+3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for (x^2+3)(x^3+2x^2+3x+6)+(2x^3+3)= equation:

Simplifying
(x2 + 3)(x3 + 2x2 + 3x + 6) + (2x3 + 3) = 0

Reorder the terms:
(3 + x2)(x3 + 2x2 + 3x + 6) + (2x3 + 3) = 0

Reorder the terms:
(3 + x2)(6 + 3x + 2x2 + x3) + (2x3 + 3) = 0

Multiply (3 + x2) * (6 + 3x + 2x2 + x3)
(3(6 + 3x + 2x2 + x3) + x2(6 + 3x + 2x2 + x3)) + (2x3 + 3) = 0
((6 * 3 + 3x * 3 + 2x2 * 3 + x3 * 3) + x2(6 + 3x + 2x2 + x3)) + (2x3 + 3) = 0
((18 + 9x + 6x2 + 3x3) + x2(6 + 3x + 2x2 + x3)) + (2x3 + 3) = 0
(18 + 9x + 6x2 + 3x3 + (6 * x2 + 3x * x2 + 2x2 * x2 + x3 * x2)) + (2x3 + 3) = 0
(18 + 9x + 6x2 + 3x3 + (6x2 + 3x3 + 2x4 + x5)) + (2x3 + 3) = 0

Reorder the terms:
(18 + 9x + 6x2 + 6x2 + 3x3 + 3x3 + 2x4 + x5) + (2x3 + 3) = 0

Combine like terms: 6x2 + 6x2 = 12x2
(18 + 9x + 12x2 + 3x3 + 3x3 + 2x4 + x5) + (2x3 + 3) = 0

Combine like terms: 3x3 + 3x3 = 6x3
(18 + 9x + 12x2 + 6x3 + 2x4 + x5) + (2x3 + 3) = 0

Reorder the terms:
18 + 9x + 12x2 + 6x3 + 2x4 + x5 + (3 + 2x3) = 0

Remove parenthesis around (3 + 2x3)
18 + 9x + 12x2 + 6x3 + 2x4 + x5 + 3 + 2x3 = 0

Reorder the terms:
18 + 3 + 9x + 12x2 + 6x3 + 2x3 + 2x4 + x5 = 0

Combine like terms: 18 + 3 = 21
21 + 9x + 12x2 + 6x3 + 2x3 + 2x4 + x5 = 0

Combine like terms: 6x3 + 2x3 = 8x3
21 + 9x + 12x2 + 8x3 + 2x4 + x5 = 0

Solving
21 + 9x + 12x2 + 8x3 + 2x4 + x5 = 0

Solving for variable 'x'.

The solution to this equation could not be determined.`